DIRECT EMPIRICAL TEACHING INDONESIAN FOR FOREIGNERS: TEACHING TECHNIQUES AND HINDRANCES - Syafryadin Syafryadin; Feny Martina (Balai Diklat Keagamaan Bandung, 2021)
This study aims to know teaching techniques applied by English teachers who taught Indonesian for foreigners (BIPA) as several hindrances were encountered such as material decision, terms of Indonesian grammar, characters of foreigners, reading mastery, lack of vocabulary and its use, and so on. The descriptive qualitative was employed by the researcher. The sample was 15 teachers who practiced teaching Indonesian for 15 foreigners in Bengkulu. The methods for collecting the data were using observation checklist and interview guidelines. The collected data were analysed qualitatively by using content analysis. The results showed that teachers employed several teaching techniques. The second, the problems encountered by teachers were lack of experience, low language knowledge, inappropriate method or technique, and age, while the students’ problems were less practice or exposure, mispronunciation, lack of vocabulary, grammatical understanding, and age. This research suggests that the teachers should teach Indonesian in more effective and efficient techniques.Keywords: Teaching Indonesian; Beginner; Teaching techniques; Hindrances